Jesus in Sacred Art through the Lenses of a Specialist in Theatre Studies - Ana-Magdalena Petraru (Anastasis: Research in Medieval Culture and Art, 2023)
Book review: George Banu, il. de Mirela Marin, Iisușii mei sau coexistența cu arta sacră/ My Jesuses or Coexistence with Sacred Art, Nemira, Bucharest, 2018, 160 pages